Stereospecific Synthesis of (Z, Z)‐Isobenzofurans via Radical‐Enabled Cleavage of C(sp3)−C(sp3) and C(sp2)‐Halogen Bonds. Issue 23 (30th October 2019) - Huang, Min‐Hua; Shi, Hao‐Nan; Zhu, Chi‐Fan; He, Chun‐Lan; Hao, Wen‐Juan; Tu, Shu‐Jiang; Jiang, Bo
Abstract: A novel radical‐induced annulation/1, 8‐halosulfonylation of β‐alkynyl ketones with haloaryl diazonium tetrafluoroborates and DABCO . bis(sulfur dioxide) was first achieved via the cleavage/recombination of C( sp 3 )−C( sp 3 ) and C( sp 2 )‐halogen bonds, from which 47 examples of sulfone‐containing 1, 3‐dimethylene‐substituted ( Z, Z )‐isobenzofurans as single stereoisomers were synthesized in generally good yields. This multicomponent pathway is proposed to proceed through the in‐situ generation of arylsulfonyl radicals, followed by selective radical addition‐cyclization and ring‐opening of the cyclopropyl unit as well as C( sp 2 )‐halogen bond cleavage, resulting in the consecutive construction of three new chemical bonds, including C−S, C−O and C‐halogen bonds. Abstract :